The clinical significance of the MIF homolog d-dopachrome tautomerase (MIF-2) and its circulating receptor (sCD74) in burn. Issue 6 (September 2016) - Kim, Bong-Sung; Stoppe, Christian; Grieb, Gerrit; Leng, Lin; Sauler, Maor; Assis, David; Simons, David; Boecker, Arne Hendrick; Schulte, Wibke; Piecychna, Marta; Hager, Stephan; Bernhagen, Jürgen; et al.
Highlights: DDT and sCD74 serum and mRNA levels are increased in burn patients. DDT is a potential biomarker for burn sepsis and a predictor for lethal outcome. sCD74 may rather be used to monitor burn patients due to its delayed up-regulation. Abstract: Background: We reported earlier that the cytokine macrophage migration inhibitory factor (MIF) is a potential biomarker in burn injury. In the present study, we investigated the clinical significance of the newly discovered MIF family memberd -dopachrome tautomerase (DDT or MIF-2) and their common soluble receptor CD74 (sCD74) in severely burned patients. Methods: DDT and sCD74 serum levels were measured 20 severely burned patients and 20 controls. Serum levels were correlated to the abbreviated burn severity index (ABSI) and total body surface area (TBSA) followed by receiver operating characteristic (ROC) analysis. Data were supported by gene expression dataset analysis of 31 burn patients and 28 healthy controls. Results: CD74 and DDT were increased in burn patients. Furthermore, CD74 and DDT also were elevated in septic non-survivors when compared to survivors. Serum levels of DDT showed a positive correlation with the ABSI and TBSA in the early stage after burn, and the predictive character of DDT was strongest at 24 h. Serum levels of CD74 only correlated with the ABSI 5 days after injury. Conclusions: DDT may assist in the monitoring of clinical outcome and prediction of sepsis during the early post-burn period. Soluble CD74 and MIF, by contrast, have limited value as an early predictor of death due to their delayed response to burn.